2016
DOI: 10.3923/pjbs.2016.71.76
|View full text |Cite
|
Sign up to set email alerts
|

Alteration Expression of Bax, Bcl-2 and VDAC1 Genes in Oligozoospermic and Fertile Subjects

Abstract: One of factors causing oligozoospermic circumstances is excessive apoptosis during spermatogenesis. Spermatogenesis known involves Bcl-2 family proteins in cytoplasm and Voltage Dependent Anion Channel 1 (VDAC1) in outer mitochondrial membrane to facilitate releasing of apoptosis factor such as cytochrome-c from inter-membrane space into cytoplasm. The study was aimed to analyze the mRNA expression of pro-apoptotic Bax, anti-apoptotic Bcl-2 and VDAC1 genes derived from 45 oligozoospermic subjects and 20 fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Meanwhile, both voltage-dependent anion channel-1 (VDAC1) and −2 (VDAC2) are capable of forming stable and highly conductive voltage-gated channels, which provide the major passage for the transportation of ions and metabolites across the mitochondrial outer membrane [ 44 ]. Moreover, the abundances of VDAC1 and VDAC2 are closely related to spermatogenesis [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, both voltage-dependent anion channel-1 (VDAC1) and −2 (VDAC2) are capable of forming stable and highly conductive voltage-gated channels, which provide the major passage for the transportation of ions and metabolites across the mitochondrial outer membrane [ 44 ]. Moreover, the abundances of VDAC1 and VDAC2 are closely related to spermatogenesis [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Likewise, Amir et al reported that the altered expressions of pro-apoptotic Bax and voltage-dependent anion channel 1, and anti-apoptotic Bcl-2 are linked to oligozoospermia. 22 However, the molecular mechanism underlying apoptosis in spermatogenesis has not been completely elucidated and requires further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VDAC1 enhanced oxidative stress-induced apoptosis in cerebellar granule neurons (Liao et al, 2015). Amir and colleagues conducted a clinical trial and found that the mRNA levels of Bax and VDAC1 were significantly elevated in spermatozoa from oligozoospermia patients compared to that in the fertile donors (Amir et al, 2016). Deletion of cystic fibrosis transmembrane conductance regulator (CFTR), an important regulator of male fertility, slightly increased VDAC1 expression in mice testis.…”
Section: Introductionmentioning
confidence: 99%